Diagnosis and Treatment of Infected Shoulder Arthroplasty: Current Concepts Review - Marcheggiani Muccioli, Giulio Maria; Guerra, Enrico; Roberti di Sarsina, Tommaso; Alesi, Domenico; Fratini, Stefano; Cammisa, Eugenio; Rinaldi, Vito Gaetano; Lullini, Giada; Rotini, Roberto; Zaffagnini, Stefano (Joints, 2018)
Periprosthetic shoulder infection (PSI) is an emerging pathology which requires many improvements in diagnosis and treatment to obtain a satisfying success rate. Different approaches have been described. This article summarizes current concepts of diagnostic process and main treatments described in the literature.
Keywords: infection; shoulder; prosthesis; diagnosis; treatment